Developing faculty in liberal arts colleges : aligning individual needs and organizational goals - Baker, Vicki L., 1978-; Lunsford, Laura Gail; Pifer, Meghan J., 1978- (American campus., 2017)
"Developing Faculty Members in Liberal Arts Colleges analyzes the career stage challenges these faculty members must overcome, such as a lack of preparation for teaching, limited access to resources and mentors, and changing expectations for excellence in teaching, research, and service to become academic leaders in their discipline and at these distinctive institutions. Drawing on research conducted at the thirteen institutions of the Great Lakes Colleges Association, Vicki L. Baker, Laura Gail Lunsford, and Meghan J. Pifer propose a compelling Alignment Framework for Faculty Development in Liberal Arts Colleges to show how these colleges succeed--or sometimes fail--in providing their faculties with the right support to be successful"--